INCREASING STUDENTS' CAPACITY IN FLOOD DISASTER THROUGH LEARNING WITH PROBLEM-BASED LEARNING MODEL WITH RELIGIOUS BEHAVIORISTIC APPROACH - Ode Sofyan Hardi; Cahyadi Setiawan; Aida Makbullah; Andhini Swarna Dyah Puspita; Muhammad Naufal Azhar (Universitas Sebelas Maret (UNS), 2025)
This research examined the enhancement of students' preparedness in facing disasters, particularly flood disasters, through the integration of Problem-Based Learning (PBL) and a behavioristic-religious approach. The research aimaned to understand how religious values and behavioristic teaching methods could improve students' awareness and capacity to effectively respond to flood disasters. A qualitative research methodology was employed, with data collected through interviews, observations, focus discussions (FGD) and document analysis from teachers and students in elementary schools. The data were analyzed using triangulation with disaster and religious experts. The findings indicate that disaster education knowledge utilizing a behavioristic-religious approach was generally well understood by school stakeholders, including teachers, principals, and school boards, with 86% demonstrating a good understanding. However, some informants had limited understanding of this approach, highlighting the need for broader implementation not only among students but also among school stakeholders. Additionally, the majority (around 80%) of respondents identified lectures and Q&A sessions as effective teaching methods, while only a small portion emphasized the importance of simulations reinforced with religious values. Regardless of these benefits, issues such as curriculum mapping, teacher training, and the inclusion of religious instruction to accommodate diverse student backgrounds. This research concluded that the integration of PBL with religious behavioristic reinforcement improved disaster literacy, preparedness, and spiritual resilience among students. Future studies should investigate hybrid models integrating behaviorism with other student-centered learning approaches to further maximize disaster education strategies.